An experimental study on beer distribution game : impact of inventory visibility and business intelligence on supply chain - Li, Xiang (2014)
This project examined the impact of inventory visibility and business intelligence on supply chain by carrying out a series of experiments based on the popular Beer Distribution Game. These experiments are conducted in the context of simple, serial supply chain with 4 echelons at two institutions ofhigher learning in Singapore. Instead of implementing the experiments in the traditional board or online beer game setting, a modified model of the game was developed. The experiment was conducted as a business competition whereby participants physically involved in the supply-chain business of selling fast moving consumer products (FMCG).